(untitled) (Journal of Fatima Jinnah Medical University, 2019)
According to World Health Organization (WHO) 400 million people are affected by viral hepatitis with 6 10 million new cases every year.1 Majority of them are residing in developing countries. Besides hepatitis B and C, large number of people suffer hepatitis A and E every year. The periodic outbreaks of hepatitis A and E in countries with poor resource settings is a serious public health issue, which is potentially avoidable. Hepatitis E is a self-limiting, enterically transmitted infection caused by the hepatitis E virus (HEV). The genotypes of HEV have a unique geographical distribution. Genotype 1 is most prevalent in Asia and North Africa and appears to be more virulent than genotype 3 and 4 prevalent in Europe and United States. Majority of the people acquire infection by using fecally contaminated water. Other identified routes of transmission are ingestion of undercooked or uncooked meat products, infected blood transfusion and vertical materno-fetal transmission. The overall case fatality rate varies from 4% in general population to 20- 25 % in pregnancy. The disease acquired during second and third trimester usually run a stormy course leading to poor maternal and fetal outcome. It has been reported that up to 70% of pregnant women with acute hepatitis E rapidly progress to acute liver failure with a short pre-encephalopathy period.